Checkpoint kinase 1 expression is an adverse prognostic marker and therapeutic target in MYC-driven medulloblastoma - Prince, Eric W.; Remke, Marc (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.10692 Eric W. Prince, Ilango Balakrishnan, Monil Shah, Jean M. Mulcahy Levy, Andrea M. Griesinger, Irina Alimova, Peter S. Harris, Diane K. Birks, Andrew M....